Burnout – An Exponential Rise (Journal of Organizational Psychology, 2023)
Mental health at workplaces has taken a new dimension since the pandemic spread across the world. This research paper is an exploratory paper to understand the impact of COVID-19 on workplaces and their employees in the context of mental health. The pandemic highlighted the need to look at human beings as a whole self. Mental health became a reality as felt in waves of the Great Resignation movement. Burnout was experienced by many employees who were working already in high-pressure jobs pre-COVID. This study explores the impact of pandemic on health care workers (HCW) in hospitals and academics working in the tertiary sector in Australia. This is a qualitative study based on secondary research and partly based on the lived experience of the author. This paper delves into the causes of workplace stress and its impact on well-being of the workforce. Some strategies for managing these issues are recommended. Limitations of the paper include limited research and only two industry sectors in Australia are explored as part of this research.
Keywords: organizational psychology; physical health; mental health; spiritual health; social health- social capital; financial health; well-being at work; hybrid workplaces; post-COVID-19; the Great Resignation movement; burnout; checkout at work; walkouts; workplace stressors; health sector; higher education sector